# Given #g(x) = 7x - 2# and #h(x) = 4x^2 + 7# how do you find (g + h)(-3)?

To find (g + h)(-3), you first evaluate g(-3) and h(-3) separately, then add the results together.

g(-3) = 7(-3) - 2 = -21 - 2 = -23 h(-3) = 4(-3)^2 + 7 = 4(9) + 7 = 36 + 7 = 43

(g + h)(-3) = g(-3) + h(-3) = -23 + 43 = 20

By signing up, you agree to our Terms of Service and Privacy Policy

Function operations are just as in arithmetic; when adding functions, for example, you must add the functions, combining like terms.

Hopefully this helps!

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- The product of two consecutive integers is 482 more than the next integer. What is the largest of the three integers?
- How do you find 4x - 2y - z, if x = 2, y = 3, and z = -8?
- How do you evaluate #(5wx)/z# if w=6, x=0.4, y=1/2, z=-3?
- How do you write using variables: Ten is seven more than a number?
- How do you simplify #4+6/2+3#?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7